2002
DOI: 10.1108/00483480210438753
|View full text |Cite
|
Sign up to set email alerts
|

Liking and similarity as predictors of multi‐source ratings

Abstract: This study explored the ability of liking and two forms of rater-ratee similarity to predict multi-source proficiency ratings of managerial competencies. Findings from the regression model that included all raters indicated that technical proficiency, rater-ratee liking, demographic and attitudinal similarity about work all were significant predictors of proficiency ratings. For these ratings, attitudinal similarity was the strongest predictor of ratings after technical proficiency. Liking, attitudinal and dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…As reviewed in the introduction, it is possible that a portion of this relationship is attributable to performance irrelevant factors such as rater cognitive and affective biases, performance-irrelevant friendship, rater personality, ratee demographics, ratee attractiveness, surface or deep level similarity, or lack of familiarity with ratee performance. However, Bates (2002) found that even after controlling for such performance irrelevant factors, liking is still strongly related to performance ratings. Additional research comparing the relative influence of rater and ratee factors that might introduce liking-induced bias is needed, as is accompanying research isolating methods to reduce any performance irrelevant influence of rater bias on performance ratings.…”
Section: Main Findings and Implicationsmentioning
confidence: 85%
“…As reviewed in the introduction, it is possible that a portion of this relationship is attributable to performance irrelevant factors such as rater cognitive and affective biases, performance-irrelevant friendship, rater personality, ratee demographics, ratee attractiveness, surface or deep level similarity, or lack of familiarity with ratee performance. However, Bates (2002) found that even after controlling for such performance irrelevant factors, liking is still strongly related to performance ratings. Additional research comparing the relative influence of rater and ratee factors that might introduce liking-induced bias is needed, as is accompanying research isolating methods to reduce any performance irrelevant influence of rater bias on performance ratings.…”
Section: Main Findings and Implicationsmentioning
confidence: 85%
“…Korrelationen zwischen den Erfolgschancen von Bewerberinnen und dem Frauenanteil bei den Gatekeepern wurden bisher bei Berufungsverfahren gefunden: Je mehr Frauen im Berufungskomitee sind, umso höher ist die Wahrscheinlichkeit, dass eine Frau die Professorenstelle erhält [5,12,41,42]. Diese Korrelation belegt jedoch nicht zwangsläufig, dass Frauen Frauen fördern.…”
Section: Ff3: Fördern Frauen Frauen?unclassified
“…However, the evidence suggests that this expectation is unlikely to be fulfilled. Interpersonal factors such as liking and similarity have been found to be more important in determining ratings in 360-degree appraisals than the technical proficiency of the person being appraised (Bates, 2002). We also now live in an increasingly litigious age.…”
Section: The Perspective Of the Interviewermentioning
confidence: 99%
“…It is assumed that appraisals from multiple sources provide a wider range of performance information, useful in identifying employee strengths and weaknesses (Gregurus et al, 2001). They are also assumed to have the capacity to increase perceived fairness, reliability and ratee acceptance of feedback (Harris and Schaubroeck, 1988), to provide an additional legal defence in the face of feedback (Bernardin and Beatty, 1984), and to be more simple and inexpensive to administer (Bates, 2002). In essence, applause or boos from a large audience is thought to deliver a more credible verdict on a performance than that of a single spectator.…”
Section: -Degree Appraisal -A New Way Forward?mentioning
confidence: 99%
See 1 more Smart Citation